O Impacto das variações cambiais nas exportações do milho e do algodão - Souza, Dallas Kelson Francisco de (2018)
Since the begining of the 21st century, the exports of corn and cotton have increased, increasing the Brazilian participation in these international markets. In addition to the technological changes incorporated to the cultivation of these crops, this performance can also be attributed in part to the bigger competitiveness in the international market due to the devaluation of the exchange rate started in January of 1999. The objective of the present study is to evaluate the main determinants of the exported quantum of these crops, with emphasis on the influence of the exchange rate variations on export performance, taking in account its impact on the prices. The theoretical framework is based on the hypotheses about export supply, which assumes that agricultural exports depend largely on the domestic constraints of the exporting country. It was also adopted the theoretical concepts about the exchange rate pass-through. To reach the proposed objectives, we opted for the multivariate time series instruments. It was tested the time series stationarity conditions and performed the cointegration tests based on the methodology proposed by Johansen (1988, 1995), which allows to specificate the Vector Error Correction Model (VECM), and to separate short and long-run components. Four Vector Error Correction Models (VECM) were specified, which are: corn export supply, cotton export supply, the exchange rate pass-through to corn export prices and the pass-through rate to the cotton export prices. Additionally, these models were estimated using the Vector Structural Model of Error Correction - SVEC, consistent with the theoretical framework adopted in this research. The results indicate thatthe main determinants of maize and cotton exports were, in the long run, the crop prices. It is important to highlight the importance of the real exchange rate to raise maize exports while textile production decreases cotton exports. The exchange-rate pass-through to the maize export price was incomplete which implies that exchange rate changes influences the exporter's competitiveness. By the other side, the exchange rate pass-through was null for cotton prices, which indicates effect so that it to only impacts the exporter's mark-up. The results indicate that maize and cotton exporters obtained income gains in domestic currency when there was a devaluation in the exchange rate in the analyzed period. In summary, the Brazilian cotton market showed significant integration to the international market, as it presents a high coefficient of international price transmission.